Ontogenetic changes of lipofuscin-like pigments in the rat heart - Wilhelm, J; Ošt'ádalová, I (Physiological research, 2012)
Increased generation of reactive oxygen species results in the formation of fluorescent end-products of lipid peroxidation - lipofuscin-like pigments (LFP). LFP increased up to six-fold from the fetal value in the rat heart immediately after birth. In the experimental design of this study the fetuses were sampled 1 day before birth, and then the samples were collected on postnatal days 1, 4, 7, 10, 15, 30, and 60. Males and females were compared on day 30 and 60 when the difference between right and left ventricle was studied as well. Four LFP fluorophores were analyzed: F355/440, F310/470, F350/450, F315/450 (excitation/emission, nm). All fluorophores decreased on day 4 relative to day 1, subsequent transient increases ended in a significant decrease on day 60. However, the LFP levels on day 60 are still about threefold higher than those in fetuses. Differences between male and female hearts were observed on day 30. The corresponding male ventricles contained by one third higher concentration of LFP than the female counterparts. The increase in LFP concentration in male ventricles on day 30 was only transient, no difference between corresponding male and female ventricles was found on day 60. The most distinguished feature in the male heart was a sharp LFP decrease in the right ventricle on day 60.
Keywords: Lipofuscin; Female; novorozená zvířata; peroxidace lipidů; krysa rodu Rattus; zvířata; potkani Wistar; lipofuscin; Animals, Newborn; ženské pohlaví; Rats, Wistar; Male; Heart; Rats; myokard; Animals; Myocardium; mužské pohlaví; Lipid Peroxidation; srdce